Reconstructing Islamic Education Governance through Pesantren Values: A Multi-Site Model for Building Globally Competitive Islamic Boarding Schools - Abdul Halim; Syamsun Niam; Ahmad Muhtadi Anshor; Syahril Siddik; Mujamil Mujamil; Kojin Kojin (Al-Qalam Institue, 2025)
This study aims to reconstruct Islamic education governance through pesantren values by developing a multi-site governance model that strengthens institutional excellence and global competitiveness. The research responds to the growing need for governance frameworks that preserve the philosophical identity of Islamic boarding schools while adapting to educational transformation in the digital and global era. A qualitative approach with a multi-site case study design was employed at Salafiyah-Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo, and Al Qodiri Islamic Boarding School in Jember, Indonesia. Data were collected through in-depth interviews, participant observation, document analysis, and field notes, and analyzed using the interactive model of data condensation, data display, and conclusion verification. The findings reveal that effective Islamic education governance is built upon the integration of value-based leadership, pesantren organizational culture, strategic educational management, integrated curriculum, professional human resource development, collaborative governance, and continuous quality assurance. These interconnected components contribute significantly to institutional innovation, educational quality, organizational resilience, and graduate competitiveness. The study proposes a Pesantren-Based Islamic Education Governance Model as its primary theoretical contribution, demonstrating that traditional Islamic values can serve as strategic organizational resources for sustainable institutional transformation. The findings imply that educational policymakers and pesantren leaders should integrate religious values with contemporary governance practices to strengthen institutional performance and prepare globally competitive graduates while preserving the authentic identity of Islamic boarding schools.